2001
DOI: 10.1002/1522-2683(200105)22:9<1724::aid-elps1724>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

The proteome of maize leaves: Use of gene sequences and expressed sequence tag data for identification of proteins with peptide mass fingerprints

Abstract: As a first step in establishing a proteome database for maize, we have embarked on the identification of the leaf proteins resolved on two-dimensional (2-D) gels. We detected nearly 900 spots on the gels with a pH 4-7 gradient and over 200 spots on the gels with a pH 6-11 gradient when the proteins were visualized with colloidal Coomassie blue. Peptide mass fingerprints for 300 protein spots were obtained with matrix assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometer and 149 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 26 publications
3
97
0
4
Order By: Relevance
“…Protein separation by 2-DE is known to have physical limitation in separating proteins, where proteins of extreme pIs and Mr are excluded from the 2-DE profiles [42,43]. Limited Mr range of 2-DE electrophoresed spots has also been reported in other studies of the proteome of maize (Zea mays) leaves [44] and cell suspension cultures [45] as well as different tissues [46] of barrel medic (Medicago truncatula), amongst others. The IEF pH restriction of 4-7 in sorghum leaf proteome has also been previously reported [23].…”
Section: -De Image Analysis and Annotation Of Stress-responsive Protmentioning
confidence: 64%
“…Protein separation by 2-DE is known to have physical limitation in separating proteins, where proteins of extreme pIs and Mr are excluded from the 2-DE profiles [42,43]. Limited Mr range of 2-DE electrophoresed spots has also been reported in other studies of the proteome of maize (Zea mays) leaves [44] and cell suspension cultures [45] as well as different tissues [46] of barrel medic (Medicago truncatula), amongst others. The IEF pH restriction of 4-7 in sorghum leaf proteome has also been previously reported [23].…”
Section: -De Image Analysis and Annotation Of Stress-responsive Protmentioning
confidence: 64%
“…However, using MS and advanced methods of database interrogation, it is becoming increasingly possible to study the proteomes of organisms with unsequenced genomes. Cross-species identifications have been made in these organisms and others not cited: Zea mays [46,47], Pisum sativum [48,49], Papaver somniferum [50], Spinacia oleracea [44], Arabidopsis thaliana [44], Bos taurus [51], Xenopus laevis [30,52], Pichia pastoris [25], and Trypanosoma brucei [28,29]. Many earlier studies utilizing cross-species identification of unknown proteins relied on high mass accuracy MALDI peptide mapping, and therefore may have identified proteins or enzymes highly conserved across the biosphere.…”
Section: Developments In Genomic Sequencing and The Study Of Proteomementioning
confidence: 99%
“…Many biological researchers investigating proteomes have already experienced the lack of genomic resources as an inability to identify proteins by MS. For example, proteomic studies in maize, an economically important organism, have been compromised due to the lack of database resources and an inability to use available database resources effectively [47]. However, plant scientists have begun to realize the limitations of non-error-tolerant methods of protein identification and now see the prospects of sequence similarity methods to contribute to proteomics [47,55].…”
Section: Perspective: Proteomics and Phylogenetic Considerations For mentioning
confidence: 99%
“…The protein pellet was suspended in a rehydration buffer [7M urea, 2M thio-urea, 4% (w/v) CHAPS, 1% (w/v) DTT and 2% (v/v) Pharmalyte pH [3][4][5][6][7][8][9][10]. The suspension was sonicated at 18-20°C for 30 min and centrifuged at 190,000Xg for 30 min in a Beckman Airfuge Ultracentrifuge (Beckman Coulter Inc, Fullerton, CA, USA).…”
Section: Protein Solubilization and Quantificationmentioning
confidence: 99%
“…The selection of this pH range was based on the results of our preliminary study, which revealed that more than 95% of the soluble proteins in corn cultivar, Trucker's Favorite White, had an isoelectric point in the range of pH 4 to 7 (data not shown). Previous studies with other corn lines had reported the majority of corn proteins having an isoelectric point in this pH range [8,9]. The protein maps for the chinch bug-infested and healthy corn seedlings are presented in the Figs.…”
Section: Comparison Of Two Dimensional Protein Mapsmentioning
confidence: 99%